O desafio da construção da "cidade de todos": a experiência do Plano Diretor Participativo de Pacatuba-CE - Costa, Maria do Socorro Vieira (2009)
This research intends to evaluate the conquests and impasses identified in the revision of the Managing Plan of the city of Pacatuba while space of participation of the civil society in the processes of governmental decisions, leading in consideration three important determinative: the envolvement of the municipal public power, the paper of the civil society and the adopted institucional format in this municipal experience. These three factors are considered by some theoreticians (LUCHMANN, 2000; AVRITZER, 2008) as determinative for implementation and success of these participativos models.